Quality in the 21st Century Perspectives from ASQ Feigenbaum Medal Winners - Sampaio, Paulo; Saraiva, Pedro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is a compilation of perspectives provided by several winners of the ASQ Feigenbaum Medal, which is awarded each year to an individual under the age of 35 who has made a significant contribution to the field of Quality. As such, it serves as a valuable reference book in this area. It is primarily based on the medalists' vision to "refresh" and "re-think" the quality concepts that have been used over the past century and the future development of the topic. Maximizing readers' understanding of the ways in which Quality is created, it provides insights from pioneers in this field from around the globe and anticipates how and what Quality will be in the future, as well as how people and organizations can benefit from it today.
Introduction -- Quality: From Past Perfect to Future Conditional -- Importance of Data Quality for Analysis -- The Future of Quality: Strategy, Leadership, and an Opportunity to Improve Quality of Life on a Global Scale there to be Seized or Lost -- Common Sense, Use the Right Tool for the Job -- Development of Strategic Quality Metrics for Organizations Using Hoshin Kanri -- Customer Experience Driving Quality Transformation -- The Role of Learning and Exploration in Quality Management and Continuous Improvement -- The Efficienti: Quality Professionals of the 21st Century -- Final Thoughts -- Feigenbaum Medalists (Non-Authors) Short Bios.
Keywords: Security systems; Technological innovations; Computers; Security Science and Technology; Innovation and Technology Management; Hardware Performance and Reliability